(3CSFdI Ydi LeY GdLhGeYs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3EHQGgje Hf eMehO Hf Ydi GdYQV GdTGaYi s)
(3ChdgG (B:s
(3hgPg GSFdI CNQi Ydi LeY GdLhGeY HYK HgG Edi GdTjN s
(3BNQgG (B:s
(3hdcfg djS aQYkG ai gPG GdbjGS GdPi jQGg EKHGJ GdMce ajg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3CUhd Gdabgs